Mindful Echo-Journaling sebagai Intervensi Inovatif untuk Menurunkan Prokrastinasi Akademik di Era Digital - Fatimah Zahra; Meilia Ishar; Meti Puspitasari (Universitas Darul Ulum, 2026)
Academic procrastination in the digital era has increased due to social media distractions, information overload, and low mindfulness in managing attention. This study aims to examine the effectiveness of the Mindful Echo-Journaling program as a mindfulness-based strategy to reduce academic procrastination among college students. A quasi-experimental pretest–posttest design with two groups was used, consisting of an experimental group that received the intervention and a control group that did not. The Procrastination Assessment Scale for Students (PASS) was employed for measurement. The results showed a significant decrease in procrastination scores in the experimental group, from 73.94 to 59.78 (t(18)=7.78, p<0.05), while the control group showed no significant change (t(18)=-0.26, p>0.05). An independent t-test also indicated significant differences between the two groups (t(36)=-2.826, p=0.008). In conclusion, the Mindful Echo-Journaling program is effective in reducing academic procrastination among students and holds promise as an applicable mindfulness-based intervention in higher education settings.